Helene Bauer in Vienna : Political Economy Between Two World Wars - Larise, Dunja (Historical Materialism Book Series, 2025)
The year is 1914-a highly unusual time for a Polish Jewish woman to leave her husband and children and relocate to Vienna. Yet Helene Gumplowitz Landau takes this bold step, driven by her unwavering passion for socialism and her love for Otto Bauer, a leading Austrian Marxist a decade her junior. In the intellectual circles of Vienna's First Republic, Helene Bauer emerges as a prominent Marxist economist and social scientist. She becomes one of the first female economists to challenge the founding figures of neoliberalism, Ludwig von Mises and Friedrich Hayek. She critiques Otto Neurath for the flaws in his vision of a moneyless economy, confronts Ottmar Spann-Austria's foremost philosopher and ideologue of the fascist corporatist state-and is among the earliest voices warning that the Great Depression could fuel the rise of fascism. Helene Bauer spent her final years in exile in the United States, her contributions largely forgotten in Austria's Second Republic. Yet, a century later, her incisive analyses of the crises of her time remain strikingly relevant, offering profound insights into the challenges of today.